Enantioselective Interactions of Anti-Infective 8-Aminoquinoline Therapeutics with Human Monoamine Oxidases A and B - Narayan D. Chaurasiya; Haining Liu; Robert J. Doerksen; N. P. Dhammika Nanayakkara; Larry A. Walker; Babu L. Tekwani (MDPI AG, 2021)
8-Aminoquinolines (8-AQs) are an important class of anti-infective therapeutics. The monoamine oxidases (MAOs) play a key role in metabolism of 8-AQs. A major role for MAO-A in metabolism of primaquine (PQ), the prototypical 8-AQ antimalarial, has been demonstrated. These investigations were further extended to characterize the enantioselective interactions of PQ and NPC1161 (8-[(4-amino-1-methylbutyl) amino]-5-[3, 4-dichlorophenoxy]-6-methoxy-4-methylquinoline) with human MAO-A and -B. NPC1161B, the (R)-(−) enantiomer with outstanding potential for malaria radical cure, treatment of visceral leishmaniasis and pneumocystis pneumonia infections is poised for clinical development. PQ showed moderate inhibition of human MAO-A and -B. Racemic PQ and (R)-(−)-PQ both showed marginally greater (1.2- and 1.6-fold, respectively) inhibition of MAO-A as compared to MAO-B. However, (S)-(+)-PQ showed a reverse selectivity with greater inhibition of MAO-B than MAO-A. Racemic NPC1161 was a strong inhibitor of MAOs with 3.7-fold selectivity against MAO-B compared to MAO-A. The (S)-(+) enantiomer (NPC1161A) was a better inhibitor of MAO-A and -B compared to the (R)-(−) enantiomer (NPC1161B), with more than 10-fold selectivity for inhibition of MAO-B over MAO-A. The enantioselective interaction of NPC1161 and strong binding of NPC1161A with MAO-B was further confirmed by enzyme-inhibitor binding and computational docking analyses. Differential interactions of PQ and NPC1161 enantiomers with human MAOs may contribute to the enantioselective pharmacodynamics and toxicity of anti-infective 8-AQs therapeutics.